2018
DOI: 10.1186/s13104-018-3914-4
|View full text |Cite
|
Sign up to set email alerts
|

Proteinase K treatment improves RNA recovery from thyroid cells fixed with liquid-based cytology solution

Abstract: ObjectiveFine-needle aspiration biopsy (FNAB), an important diagnostic tool given its simplicity, safety, and cost-effectiveness, is fast becoming a popular procedure in the diagnosis of thyroid diseases. Generally, cells isolated from biopsies are transferred directly to microscope slides to prepare smears for cytopathological examination; however, the technical difficulties of this procedure often cause poor reproducibility, which limits the accuracy of diagnostic results. Liquid-based cytology (LBC), in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…According to Jikuzono et al 40 , proteinase k is generally employed with 0.5% SDS at 400 mg/ml in nucleic acid production at pH 7.5-8.0 and 55 °C incubation 40 . The study's findings demonstrated that using 20 µl of proteinase K (20 mg/ml) in 10% SDS at pH 7.8 and 65 °C for 90 minutes will raise the extraction yield.…”
Section: Resultsmentioning
confidence: 99%
“…According to Jikuzono et al 40 , proteinase k is generally employed with 0.5% SDS at 400 mg/ml in nucleic acid production at pH 7.5-8.0 and 55 °C incubation 40 . The study's findings demonstrated that using 20 µl of proteinase K (20 mg/ml) in 10% SDS at pH 7.8 and 65 °C for 90 minutes will raise the extraction yield.…”
Section: Resultsmentioning
confidence: 99%
“…One limitation of our study is that specimens were isolated by surgical resection. Therefore, the applicability of the results to specimens obtained by core-needle aspiration biopsy should be validated as described previously [ 9 ]. Another limitation is the small sample size.…”
Section: Limitationsmentioning
confidence: 99%
“…Interestingly, aberrant expression patterns of some ncRNAs are associated with cancer [6,7]; this suggests that ncRNAs are promising diagnostic biomarkers for cancer. While previous studies have focused on the expression of coding RNAs and microRNAs [8][9][10][11], there is little information regarding expression of long ncRNAs in FTC. Therefore, this study examined possible RNA biomarkers for the molecular diagnosis of metastatic mi/ ea-FTC.…”
Section: Objectivementioning
confidence: 99%
“…Herein, we provide information regarding a mi/ea-FTC microarray dataset, which will help to identify prognostic biomarkers for predicting high risk of metastasis among patients diagnosed with mi/ea-FTC, following the initial operation. Furthermore, such biomarkers may be used to diagnose FTC in thyroid specimens obtained by fine-needle aspiration biopsy for liquid-based cytology [9]. However, we used total RNA isolated from FFPE samples, which is known to be highly degraded [12].…”
Section: Limitationsmentioning
confidence: 99%